Neltumius arizonensis (Schaeffer) (Coleoptera: Bruchidae) as a biological control agent of mesquite (Prosopis spp., Mimosaceae) in South Africa - Coetzer, Willem (Department of Biological Sciences, 2014)
Bibliography: leaves 64-69.